#8: Microbiome and immune disruption accompany mouse death in a gnotobiotic mouse model of neonatal sepsis. (28th June 2021) - Schwartz, D; Wardenburg, K; Shalon, N; Ning, J; Crofts, T; D'Souza, A; Robinson, J; Henderson, J; Warner, B; Tarr, P; Dantas, G
Abstract: Background: Premature infants frequently receive antibiotics, which diminishes gut microbial diversity and increases susceptibility to infections by antibiotic resistant pathogens. Neonates with decreased gut microbiota diversity, termed dysbiotic, have dysregulated immune systems marked by increased concentrations of circulating activated T cells and decreased concentrations of circulating neutrophils and dendritic cells. We hypothesize that antibiotics (1) enrich for pathogens within the gut, 2) promote a systemic, proinflammatory host response, and 3) cause death in an antibiotic- and microbiome-specific manner in a gnotobiotic model of preterm gut microbiota disruption. Methods: We colonized germ free (GF) dams with stools from preterm infants. Mouse pups acquire this neonatal microbiota, and at 10 days of life (DOL), we treat them with clinically-relevant doses of antibiotics subcutaneously for 3 days. We determined serum concentrations of antibiotics in 10 DOL pups using tandem mass spectrometry to achieve approximate pharmacokinetics as observed in the neonatal intensive care unit (NICU). We ascertained phylogenetic composition using metagenomic shotgun sequencing of individual pup fecal samples longitudinally. We performed flow cytometry on peripheral blood and gut permeability assays to determine the local and peripheral immune response. Results: We found adding probenecid prolonged the half-life of ampicillin and meropenem allowing for an approximation of serum levels observed in the NICU with an every 8 hour dosing regimen. Using two representative microbiomes from human neonates (hereafter referred to as microbiota A or B), we show that 95% of pups given microbiota A survive versus 54% given microbiota B after meropenem/probenecid treatment (Fig. 1A; p<0.01; n= 18–42 mice in 3–6 independent experiments). Conversely, only 28% of microbiota-A humanized pups survive during ampicillin/probenecid treatment (Fig. 1; p<0.0001). Ampicillin-resistant Klebsiella species and E. coli dominated the gut of microbiota A-humanized pups who succumbed during ampicillin/probenecid treatment whereas Enterococci dominated the gut of microbiota B-humanized pups who died during treatment. To test the reproducibility of this phenotype, we colonized mice with 2 additional preterm neonatal microbiomes with similar compositions to microbiota A and B (D and C, respectively). We found that microbiota-C humanized pups were similarly dominated by Enterococcus faecalis resulting in 42% mortality during meropenem/probenecid treatment (Fig. 1). Pups colonized with microbiota B had decreased circulating granulocytes, B cells, and CD8+ T cells at sacrifice after treatment compared to microbiota A-humanized pups. We next assessed gut permeability after antibiotic treatment by measuring 4kDa FITC-Dextran in mouse serum after oral gavage. Microbiota-A humanized pups treated with ampicillin/probenecid and microbiota B-humanized pups treated with meropenem/probenecid had elevated serum levels of FITC-Dextran (p<0.05 relative to vehicle control, one way ANOVA), indicative of increased gut permeability. Conclusions: Our model of preterm microbiota perturbation by antibiotics demonstrates increased gut permeability, proinflammatory immune response, and death dependent on the microbiota-antibiotic combination. Our transgenerational humanized-microbiota mouse model can be utilized to determine antibiotic by microbiota perturbation and examine risks of late onset sepsis from specific antimicrobial administration. This research can lead to a personalized medicine approach of antibiotic treatment in the NICU to limit antibiotic side effects and mortality.